Assessment of seawater intrusion to the agricultural sustainability at the coastal area of Carey Island, Selangor, Malaysia - Tajul Baharuddin, M.F.; Taib, S.; Hashim, Roslan; Abidin, M.H.Z.; Rahman, N.I. (2013)
Groundwater suitability for agriculture in an island with limited recharge area may easily be influenced by seawater intrusion. The aim of this study was to investigate seawater intrusion to the suitability of the groundwater for oil palm cultivation at the ex-promontory land of Carey Island in Malaysia. This is the first study that used the integrated method of geo-electrical resistivity and hydro-geochemical methods to investigate seawater intrusion to the suitability of groundwater for oil palm cultivation at two different land cover condition. The relationship between earth resistivity, total dissolved solids and earth conductivity was derived with crop suitability classification according to salinity, used to identify water types and also oil palm tolerance to salinity. Results from the contour conductivity maps show that area facing severe coastal erosion and area still intact with mangrove forest exhibits unsuitable groundwater condition for oil palm at the unconfined aquifer thickness of 15 and 31 m, respectively. Based on local sea-level rise prediction and Ghyben-Herzberg assumption (sharp interface), the condition in the study area, especially in severe erosion area, by the twenty-first century will no longer be suitable for oil palm plantation. The application of geo-electrical method combined with geochemical data, aided with the information on environmental history and oil palm physiography, has demonstrated that the integration of techniques is an effective tool in defining the status of agricultural suitability affected by salinity at the coastal aquifer area.